2007
DOI: 10.1111/j.1399-3054.2007.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the growth of spring ephemerals: Crocus vernus

Abstract: Spring ephemerals of deciduous forests appear shortly after snow melt and senesce shortly after the overstorey canopy has closed. During this short period, they take advantage of the high light conditions, but also of the low‐temperature regime that favours growth in these species. This better growth at cooler temperatures has been attributed to longer leaf life duration. The objective of this study was to test if temperature effect on growth in spring ephemerals can be explained solely by the leaf life durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 35 publications
7
44
0
Order By: Relevance
“…The decrease in the mature and senescent periods in the leaves of G. lutea in this study and E. japonicum (Yoshie and Fukuda 1994) at warm temperatures is caused by an activation of metabolic processes of the rate of aging, resulting from either a direct effect of temperature or from an indirect effect through a reduction in the sink demand as suggested by Lapointe (2001). At higher cultivation temperature corm growth of Crocus vernus stopped before the first visual sign of leaf senescence, suggesting that corm growth controls leaf longevity rather than the opposite and that growth becomes rapidly sink limited (Badri et al 2007).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The decrease in the mature and senescent periods in the leaves of G. lutea in this study and E. japonicum (Yoshie and Fukuda 1994) at warm temperatures is caused by an activation of metabolic processes of the rate of aging, resulting from either a direct effect of temperature or from an indirect effect through a reduction in the sink demand as suggested by Lapointe (2001). At higher cultivation temperature corm growth of Crocus vernus stopped before the first visual sign of leaf senescence, suggesting that corm growth controls leaf longevity rather than the opposite and that growth becomes rapidly sink limited (Badri et al 2007).…”
Section: Discussionmentioning
confidence: 76%
“…Warm air temperatures shorten the leaf longevity in Crocus vernus (Badri et al 2007) and tulips (Rees 1972). The plastic responses of summer dormancy in these plants ensure their ability to avoid hot and dry summers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that vegetative growth of spring ephemerals was terminated by the increase in soil temperature because warm temperature activated the metabolic process of aging (Badri et al 2007;Yoshie 2008). These studies suggest that growing season length of spring ephemerals may be determined by temperature regime but not by light environment.…”
Section: Is Carbon Fixation Sink-limited?mentioning
confidence: 70%
“…Spring ephemerals are well adapted to the high light conditions prevailing during early spring before trees leaf out but also to the low temperature conditions of that period. Not only do they tolerate cold temperatures, but they actually grow better under such low temperature regime and produce a larger perennial organ (Badri et al, 2007). Few studies have, however, examined the age structure of populations of spring ephemerals.…”
Section: Models To Study Aging In Perennialsmentioning
confidence: 97%